Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41531-023-00547-4
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in synucleinopathies: neuronal circuitry, underlying pathomechanisms and current therapeutic strategies

Abstract: Synucleinopathies are neurodegenerative disorders characterized by alpha-synuclein (αSyn) accumulation in neurons or glial cells, including Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA). αSyn-related pathology plays a critical role in the pathogenesis of synucleinopathies leading to the progressive loss of neuronal populations in specific brain regions and the development of motor and non-motor symptoms. Anxiety is among the most frequent non-motor symptoms in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 184 publications
1
6
0
Order By: Relevance
“… 63 Similarly, the amygdala is suggested as being affected early in PD by aSyn pathology. 60 , 64 The recent compelling hypothesis of a dichotomy in PD pathogenesis in brain first vs gut first may well be supported by our results. 65 If virus indirectly causes aSyn accumulation in highly connected hub regions, such regions may develop aSyn aggregation which could spread across the brain to connected regions in a prion like fashion, as has been demonstrated in animal models of aSyn preformed fibril inoculation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“… 63 Similarly, the amygdala is suggested as being affected early in PD by aSyn pathology. 60 , 64 The recent compelling hypothesis of a dichotomy in PD pathogenesis in brain first vs gut first may well be supported by our results. 65 If virus indirectly causes aSyn accumulation in highly connected hub regions, such regions may develop aSyn aggregation which could spread across the brain to connected regions in a prion like fashion, as has been demonstrated in animal models of aSyn preformed fibril inoculation.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the brain regions mostly affected by this biphasic response were the BLA and the Cpu, both highly connected brain regions related to early PD pathogenesis. 59 , 60 , 61 The Cpu represents the main input region from the dopamine neurons of the SNc, and dopamine loss in response to dopamine neurodegeneration is causing the hallmark motor symptoms of PD. 62 It has long been suggested that pathology may, at least in some cases, start at the dopaminergic terminals followed by cell loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety has a relative high prevalence (22.2%-66.7%) in PD patients with female being at higher risk than male patients [127][128][129]. Several kinds of anxiety are described in PD, including generalized anxiety, panic attacks, social phobia, agoraphobia, and obsessive-compulsive disorder.…”
Section: Anxietymentioning
confidence: 99%
“…Likewise, injection of αSyn preformed fibrils into the bilateral olfactory bulb of A53T transgenic mice spreads into connected regions provoking severe pathology in the hippocampus, bed nucleus of the stria terminalis and central nucleus of the amygdala. Animals exhibited hyposmia, anxiety-like behavior, and memory impairment, consequence of atrophy, neuronal loss and gliosis [131]Increase in hippocampal aSyn expression has been detected in rats with high levels of innate anxiety, suggesting that anxiety can cause aSyn accumulation, besides being a contributor of synuclein progression [129].…”
Section: Anxietymentioning
confidence: 99%